Flame acceleration and transition to detonation in a pre-/main- chamber combustion system - Lai, S; Xu, C; Davy, M; Fang, X (AIP Publishing, 2022)
Numerical simulations are performed to study the mechanism of deflagration to detonation transition (DDT) in a pre-/main- chamber combustion system. The fully compressible Navier-Stokes equations, coupled with a chemical-diffusive model in a stoichiometric ethylene-oxygen mixture, are solved with a high-order numerical algorithm on a dynamically adapting mesh. The two-dimensional simulation shows that a laminar flame grows in the pre-chamber and then develops into a jet flame as it passes through the orifice. A strong shock forms immediately ahead of the flame, reflecting off the walls, and interacting with the flame front. The shock-flame interactions are crucial for the development of flame instabilities, which trigger the subsequent turbulent flame development. The DDT arises due to an energy-focusing mechanism, where multiple shocks collide at the flame front. A chemical explosive mode analysis (CEMA) criteria is developed to study the DDT ignition mode. Preliminary one-dimensional computations for a laminar propagating flame, a fast flame deflagration, and a Chapman-Jouguet detonation are conducted to demonstrate the validity of CEMA on the chemical-diffusive model, as well as to determine the proper conditioning value for CEMA diagnostic. The two-dimensional analysis with CEMA indicates that the DDT initiated by the energy focusing mechanism can form a strong thermal expansion region that features large positive eigenvalues for the chemical explosive mode and dominance of the local autoignition mode. Thus, the CEMA criterion proposed in this study provides a robust diagnostic for identifying autoignition-supported DDT of which emergence of excessive local autoignition mode is found to be a precursor.